Tingkatkan Penjualan Online Shopping di Agribisnis: Analisis Pengaruh Bauran Pemasaran dalam Perspektif Pemasaran Agribisnis - Afriliah, Fika; Indah Purwasih, Ilka; Indriani, Novi; Nurcahyani Yahya, Septiani (Prodi Manajemen, Fakultas Ekonomi, Universitas Pamulang, 2024)
The online shopping market has become a significant global phenomenon, affecting various sectors of the economy, including agribusiness. Agribusiness, as one of the pillars in the food industry, has transformed in the face of this development. This study aims to analyze the influence of marketing mix on online shopping behavior in an agribusiness perspective. The results of this study provide valuable insights on how to increase online shopping sales in the agribusiness sector. In the digital age, a better understanding of how the marketing mix affects online consumer behavior is becoming the key to success. This research involves an in-depth analysis of the marketing strategies used in online agribusiness, providing a more comprehensive view of how agribusinesses can take advantage of opportunities in the online environment. With the insights gained from this study, agribusiness businesses can optimize their marketing strategies, adapt their products and services, and face increasingly fierce competition in the realm of online shopping. This study provides valuable guidance for agribusiness practitioners and stakeholders to respond to the challenges and opportunities that exist in the ever-evolving era of online shopping.